Desenvolvimento de software para dimensionamento de blocos rígidos sobre estacas utilizando o método das bielas e tirantes - Souza, Amanda Tavares Ribeiro de (Universidade Federal Rural do Semi-Árido, 2018)
In structural engineering, we use calculation models to perform structural calculations, and with this, the designer can perform the analysis of the structure, usually the designer has to perform this calculation successively, and doing so manually increases the probability of errors it is difficult to simulate the same project with several possible situations, which limits the more realistic knowledge about the behavior of the structure in these specific situations. This work aims to present the development of software, in Python programming language, capable of performing the analysis, dimensioning and detailing of blocks on piles according to the proposed model. This software enters the market as a computational program capable of assisting the design engineers in the proposals of structural projects, and as an alternative of error reduction, being this a tool of easy and practical application, for example, to carry out simulations of structural, without having to do the calculations manually successively times. The software was evaluated by means of comparative tests between the theoretical results and the results it presented for the same example of application of the method in practice, and obtained excellent results and excellent performance in both calculations and detailing.
Monografia
Keywords: Armadura; Detalhamento de armadura; Treliça; Python; Matplotlib; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA